The Effect of Profit and Independence on Entrepreneurial Motivation in Deli Serdang Regency Business Actors - Hanansyah, Ikhsan (Universitas Negeri Medan, 2024)
Entrepreneurship is an activity that is able to expand employment, provide broad economic services to the community, play a role in the process of equitable distribution and increase in community income, encourage economic growth, and play a role in realizing national stability. This study is a quantitative research that aims to determine the effect of two X variables, namely Profit (X1), Independence (X2), on Entrepreneurial Motivation (Y) in Sunggal Kanan Village, Sunggal District, Deli Serdang Regency. In this study, data was collected with tools in the form of questionnaires on 54 respondents, which aimed to determine respondents' responses to each variable. The analysis used includes validity tests, reliability tests, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests), multiple linear regression analysis and goodness of fit tests (F test, t test, coefficient of determination). The data obtained is the result of distributing questionnaires to respondents which are then processed using the SPSS application. The results showed that profit (tcount of 2.604) and independence (tcount of 7.372) was greater than ttable (1.675) which means that both variables partially had a positive and significant effect on entrepreneurial motivation, with the results (fcount of 31.678) greater than (ftable = 3.18), it can be concluded that profit and independence simultaneously have a positive and significant effect on entrepreneurial motivation.